Justice and legitimacy in policing : transforming the institution - Craig, Miltonette Olivia; Blount-Hill, Kwan-Lamar (Abingdon, Oxon ; New York, NY : Routledge, 2022)
"Justice and Legitimacy in Policing critically analyzes the state of American policing and evaluates proposed solutions to reform/transform the institution, such as implementing body-worn cameras, increasing diversity in police agencies, the problem of crimmigration, limiting qualified immunity, and the abolitionist movement. Considering the changes that have occurred in our socio-political climate, policymakers, scholars, and the public are in need of a book that focuses on the American policing institution in a comprehensive yet critical manner. Each chapter is devoted to a specific area of policing that has either received criticism for the problems it may create or has been proposed to effect reform. The chapters are sequenced such that readers are introduced to a spectrum of topics to expand the discourse on changes needed to achieve equitable policing. The book also encourages readers to consider the idea that achieving justice and legitimacy in policing cannot happen as the institution is now formulated, and it invites readers to use the topics discussed in each chapter to envision transformative propositions. Justice and Legitimacy in Policing is intended to engage policymakers and practitioners as well as interested members of the public. The scope of this book also makes it a valuable resource for academics and students"--
OCLC-licensed vendor bibliographic record.
Keywords: Police -- United States; Police-community relations -- United States; Police misconduct -- United States; Police administration -- United States; SOCIAL SCIENCE / Penology; SOCIAL SCIENCE / Ethnic Studies / General